A High-Fat, High-Fructose Diet Induces Antioxidant Imbalance and Increases the Risk and Progression of Nonalcoholic Fatty Liver Disease in Mice. (25th February 2016) - Jarukamjorn, Kanokwan; Jearapong, Nattharat; Pimson, Charinya; Chatuphonprasert, Waranya
Abstract : Excessive fat liver is an important manifestation of nonalcoholic fatty liver disease (NAFLD), associated with obesity, insulin resistance, and oxidative stress. In the present study, the effects of a high-fat, high-fructose diet (HFFD) on mRNA levels and activities of the antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were determined in mouse livers and brains. The histomorphology of the livers was examined and the state of nonenzymatic reducing system was evaluated by measuring the glutathione system and the lipid peroxidation. Histopathology of the liver showed that fat accumulation and inflammation depended on the period of the HFFD-consumption. The levels of mRNA and enzymatic activities of SOD, CAT, and GPx were raised, followed by the increases in malondialdehyde levels in livers and brains of the HFFD mice. The oxidized GSSG content was increased while the total GSH and the reduced GSH were decreased, resulting in the increase in the GSH/GSSG ratio in both livers and brains of the HFFD mice. These observations suggested that liver damage and oxidative stress in the significant organs were generated by continuous HFFD-consumption. Imbalance of antioxidant condition induced by long-term HFFD-consumption might increase the risk and progression of NAFLD.